EFFECTIVENESS OF STUDENT COMPANY METHOD TO GROW MOTIVATION AND ATTITUDE OF MENTAL ENTREPRENEURSHIP OF THE SMK MUHAMMADIYAH 1 BANTUL STUDENTS - Yunita Restu Ika Wulangsih; Muhammad Sayuti; Tri Kuat (Journal of Vocational Education Studies, 2018)
Student company is a program that facilitates students to form a company and manage the company with the purpose to provide experience to students to run the company's operations and conduct some business activities covering business planning, production, packaging to local and regional promotion activities. The purpose of this study to determine the effectiveness of student learning methods of student motivation in entrepreneurship, and to determine the effectiveness of student company learning methods of students' mental attitude in entrepreneurship. Based on data to be collected this research will use the type of quantitative data to know and analyze the effectiveness of student company that will affect entrepreneurship motivation and entrepreneurship mental attitude. The model used is simple regression. The results of this study indicate that the results of simple regression tests show the student company's variables, motivation and mental attitude has a significance value of 0.000, it can be concluded that student student methods are effective in influencing motivation and mental attitude of students in entrepreneurship. Adjusted R square value can be concluded the effectiveness of student company method in influencing entrepreneurship motivation is only 28.3% while the student company in influencing entrepreneurship mental attitude is only 39.3%.